EFEITO DE BORDA SOBRE A DISTRIBUIÇÃO DIAMÉTRICA EM UM FRAGMENTO DE FLORESTA OMBRÓFILA MISTA - HENTZ, Ângela Maria Klein; CORTE, Ana Paula Dalla; SANQUETTA, Carlos Roberto; BLUM, Christopher Thomas; PÉLLICO NETTO, Sylvio (Brazilian Journal of Biometrics, 2017)
The objective of this research was to evaluate the influence of edge distance in the diametric distribution of trees in an Araucaria Rainforest fragment. Data from continuous forest inventory were used in which all individuals were identified, geographically located and measured as to their diameter at breast height, considering a minimum of 10 cm. We used 3 plots of 1 ha, two of which have contact with the external edge, and the third plot is located inside the forest fragment. The plots were subdivided in subplots every 10 m after the edge, and then the individuals were plotted and analyzed. The distribution was represented by Weibull 3P function, which was well adjusted for all sub-plots. It was observed that all distributions have the negative exponential shape, characteristic of natural forests, but there was variation in the parameters of the distribution, mainly in the Fire plot, according with the edge distance. It was confirmed the existence of effects of the edge proximity in diameter distributions, although this effect is distinct in the analyzed plots, so it is believed that other parameters may change the magnitude and influence of the edge effect in the diameter distribution.